Initial stiffness of reinforced concrete structural walls with irregular openings. - Li, Bing
Reinforced concrete (RC) structural walls with openings are the primary lateral-load carrying elements utilized in many structures designed to resist earthquakes. A review of the technical literature shows that there is a considerable amount of uncertainty with regards to the elastic stiffness of these structures when subjected to seismic excitations. Current design practices often employ a stiffness reduction factor to deal with this uncertainty. In an attempt to develop additional information regarding the stiffness of these structures, this paper discusses an approach to determine the initial stiffness of RC structural walls with irregular openings and low aspect ratios. This approach would consider the effect of both flexural and shear deformations. As a part of this study, an analytical approach to determine stiffness was also developed and validated by comparing theoretical and experimental results obtained from six RC shear walls with irregular openings. Simple equations for assessing initial stiffness of RC structural walls with irregular openings are then proposed, based on these parametric case studies.
Keywords: Wall with irregular openings; Initial stiffness; Flexural stiffness; Shear stiffness; Stiffness ratio